IMPLEMENTASI SISTEM INFORMASI APLIKASI PENCATATAN INFORMASI KEUANGAN (SI APIK) BERDASARKAN SAK EMKM PADA UMKM TAPAK LAWU JUUOOS KABUPATEN MAGETAN - Yopie Diondy Kurniawan; Halleina Rejeki Putri Hartono; Yana Dwi Christanti (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2021)
Revenue and expenditure are things that cannot be separated from business actors. Receipts and expenses that occur later can be used as a basis for preparing financial reports. Preparation of financial reports is one of the important things for business actors to keep running well. The preparation of financial statements can also be used for stakeholder decision making. Increasingly advanced technological developments make the process of preparing financial statements easy. The preparation of financial reports that we generally encounter still uses hardware such as computers and laptops. Bank Indonesia, in collaboration with the Indonesian Accounting Association, has issued an application for preparing financial statements that is in accordance with SAK EMKM, namely the SI APIK application. The SI APIK application can not only be accessed via computers and laptops, but can also be accessed using smartphones. The purpose of this application is to make it easier for business actors, especially UMKM, to prepare financial reports. Tapak Lawu Juuoos is a form of UMKM that have not prepared financial reports according to standards. The reports made so far still use manual recording. This study uses data collection techniques with interviews and documentation. Interviews were conducted with UMKM owners to dig deeper about the business being undertaken and also the process of recording daily transactions. The results of the research can be used to assist the process of recording and reporting financials, so that companies can find out the resulting profit and loss.